2014
DOI: 10.1039/c3ob42464b
|View full text |Cite
|
Sign up to set email alerts
|

Reaction pathways and free energy profiles for cholinesterase-catalyzed hydrolysis of 6-monoacetylmorphine

Abstract: As the most active metabolite of heroin, 6-monoacetylmorphine (6-MAM) can penetrate into the brain for the rapid onset of heroin effects. The primary enzymes responsible for the metabolism of 6-MAM to the less potent morphine in humans are acetylcholinesterase (AChE) and butyrylcholinesterase (BChE). The detailed reaction pathways for AChE- and BChE-catalyzed hydrolysis of 6-MAM to morphine have been explored, for the first time, in the present study by performing first-principles quantum mechanical/molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…The reaction pathways of cholinesterase-catalyzed hydrolyses of heroin and 6-MAM were studied in our previous computational studies 4445 through first-principles quantum mechanics and molecular mechanics-free energy (QM/MM-FE) simulations. The optimized reactant complexes (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction pathways of cholinesterase-catalyzed hydrolyses of heroin and 6-MAM were studied in our previous computational studies 4445 through first-principles quantum mechanics and molecular mechanics-free energy (QM/MM-FE) simulations. The optimized reactant complexes (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous molecular dynamics (MD) simulations on the structures of enzyme-substrate complexes started from the X- Ray crystal structures deposited in the protein databank (PDB) (AChE: code 1B41; BChE: 2XQF and 1P0P). Molecular docking and subsequent optimization were carried out using a similar protocol described previously 44 . Briefly, the acetyl group of the substrate (heroin or 6-MAM) was positioned in the oxyanion hole (consisting of Gly116, Gly117, and Ala199 in BChE, or Gly121, Gly122, and Ala204 in AChE, or Gly116, Gly117, and Ser199 in CocH1), and the positively charged amino-group of the substrate (heroin and 6-MAM) was placed in the choline-binding site near Trp82 in BChE and CocH1 or Trp86 in AChE.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the geometry optimization at the QM/MM(B3LYP/6-31G*:CHARMM27) level was followed by single-point energy calculation at the QM/MM(B3LYP/6-311++G**:CHARMM27) level, which may be denoted as the QM/MM(B3LYP/6-311++G**:CHARMM27)//QM/MM(B3LYP/6-31G*:CHARMM27) level for convenience. Our previous QM/MM calculations on BChE-involved enzyme reactions 59 60 61 62 63 64 65 66 revealed that these QM levels (B3LYP/6-31G* for geometry optimization and B3LYP/6-311++G** for subsequent single-point energy calculations) are adequate for the QM/MM calculations on these enzymatic reaction systems.…”
Section: Methodsmentioning
confidence: 99%
“…hAChE residue in the catalytic triad, Ser203, will attack the phosphoryl group from sarin. This nucleophilic attack involves the oxygen atom of Ser203 (Qiao et al, 2014). The bond between phosphorus and fluorine becomes weaker as the partial bond forms between the oxygen in serine and the phosphorus in sarin.…”
Section: Validation Of the Autodock 4251 Tool To Perform Covalent Dockingmentioning
confidence: 99%